Assessment of diabetics by the quantification of essential elements and stable isotope ratios of carbon and nitrogen in scalp hair. (September 2019) - Hotta, Yohei; Fujino, Ryoji; Kimura, Osamu; Fujii, Yukiko; Haraguchi, Koichi; Endo, Tetsuya
Abstract: Aim: Assessment of diabetics was investigated by quantification of essential elements and δ 13 C and δ 15 N in the scalp hair, and the factors most related to the onset of diabetes identified by statistical analysis. Methods: Essential elements and δ 13 C and δ 15 N values in the hair of diabetics and controls were quantified using ICP-MS and IR-MS. Results: The Ca, Mg and Na concentrations in female controls were higher than those in male controls. Irrespective of gender, the Na and K concentrations in diabetics were higher than those in controls, while the Ca, Mg, Zn, Cu, Cr and Fe concentrations in diabetics were lower than those in controls. The δ 13 C value was significantly lower in male diabetics that in male controls. The Ca, Mg, Cr and Fe concentrations in males were positively correlated to the δ 13 C value and negatively correlated to the HbA1c value, whereas the Ca, Zn and Fe concentrations in females were positively correlated to the δ 13 C value, with a negative correlation of Zn to HbA1c value. Conclusion: Whether the subject was a diabetic or not could be determined on the basis of Zn, Cr and Na concentrations for males and Zn and Fe concentrations for females by the multiple logistic regression analysis. Highlights: We quantified essential elements and δ 13 C and δ 15 N in the hair of diabetics. Na and K concentrations tended to increase with increases in HbA1c value. Ca, Mg, Zn, Cu, Cr and Fe concentrations decreased with increases in HbA1c value. Ca, Mg, Zn, Cu, Cr and Fe concentrations decreased with decreases in δ 13 C value. Statistics imply that Zn is the most relevant element to the onset of diabetes.